Peran Orang Tua Dalam Pendidikan Anak Down Syndrome - Wulandari, Eka; Pratiwi, Enjel; Asvio, Nova (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This research aims to explore the role of parents in the education of children with down syndrome; barriers to the role of parents in the education of children with down syndrome. The research method used is a Systematic Literature Review (SLR) with six stages. The results of this research show that the role of parents in educating children with down syndrome are: a) helping develop the child’s potential, b) stimulating curiosity, c) increasing concentration, d) expanding knowledge, e) providing direct experience, f) provide opportunities to try new things, as well as g) facilitate special child development; forming the independence of children with Down syndrome, as the first and foremost educators in children’s education. Parents must also focus on being good facilitators, motivators and guides to their children. Obstacles to the role of parents in the education of children with down syndrome, namely; due to many factors a) parents of children with down syndrome face limitations in terms of costs, time and facilities, which affect their ability to provide optimal education; b) Parents do not have sufficient knowledge about this condition and how to care for their children effectively, which affects their ability to provide appropriate education; c) Parents experience stress and pressure that affects their ability to provide optimal education and affects their own quality of life; d) parents may lack support from family, friends, or the community, which affects their ability to provide optimal education; e) parents may experience psychological problems, such as depression, stress, and anxiety, which affect their ability to provide optimal education and affect their own quality of life.